Summary (Scottish Historical and Archaeological Internet Reports, 2005)
A prehistoric house was excavated in advance of industrial quarrying at Catpund, Shetland. Although little of the internal stratigraphy of the house remained beneath a modern cabbage enclosure (planticrub), the form of the house survived. The artefacts found in and around the house indicate the domestic activities which took place there, and the farming methods employed in the vicinity. A thorough analysis of the artefactual evidence suggests that the house was in use some time during the middle to late Bronze Age. This report considers the structural and environmental evidence for the house together with discussions on its form, the distribution of artefacts and dating.